Analisa Akurasi Geometri Penggunaan Metode Injection Moulding Berbasis Printer 3D Untuk Produksi Implan Pada Bedah Cranioplasty - Djoko Kuswanto; Alva Edy Tontowi; Taufik Hidayat; Agus Windharto; Arie Kurniawan (Jurnal Desain Idea: Jurnal Desain Produk Industri Institut Teknologi Sepuluh Nopember Surabaya, 2017)
Perkembangan teknologi printer 3D untuk medis, memungkinkan aplikasi produksi implan pra-operasi dengan keunggulan akurasi geometri yang baik, mengurangi waktu operasi dan resiko kehilangan banyak darah. Teknologi printer 3D paling populer dan potensial untuk dikembangkan masal di Indonenesia adalah fused deposition modeling/FDM. Akan tetapi memiliki kekurangan: single material, jenis material terbatas dan temperatur yang tinggi sehingga tidak bisa dicampur dengan material/senyawa bioaktif yang sensitif terhadap panas. Pengembangan metode injection moulding berbasis printer 3D telah dilakukan pada penelitian ini dengan melakukan modifikasi alat, material, tahapan dan sistim produksi implan pra-operasi yang mengacu pada teknologi printer 3D untuk cranioplasty yang sudah dilakukan di negara maju. Untuk memastikan modifikasi ini bisa menghasilkan implan pra-operasi dengan akurasi geometri yang diinginkan, dilakukan karakterisasi terhadap deviasi dimensi implan yang diproduksi yaitu deviasi volume, deviasi tebal, deviasi panjang linear dan deviasi sudut kelengkungan permukaan implan, pada dua metode berbeda yang diuji, yaitu metode cranial/intra operatif dan metode injection moulding dengan menggunakan material polymethylmethacrylate/ PMMA. Hasil yang didapatkan adalah deviasi volume implan yaitu sebesar 1.87 ± 1.27 % (injection moulding) dibandingkan 11.39 ± 3.71 % (metode cranial), deviasi tebal sebesar 2.54 ± 0.86 % (injection moulding) dibandingkan 7.35 ± 1.43 % (metode cranial), deviasi panjang linear sebesar 2.61 ± 0.47% (injection moulding) dibandingkan 5.76 ± 0.79 % (metode cranial) dan deviasi sudut kelengkungan permukaan sebesar 0.98 ± 0 % (injection moulding) dibandingkan 15.45 ± 3.94 % (metode cranial). Dapat diambil kesimpulan bahwa metode injection moulding lebih baik daripada metode cranial/intra operatif. Manufacture of pre-surgery implant may shorten the surgery duration and blood loss risk which provide medical benefit for patient. Additive manufacturing technology (AMT) have been applied in manufacture of pre-implant for cranioplasty surgery. Application of AMT allows production of pre-surgery implant with good geometrical accuracy. The most popular and potential printer 3D technology for mass developed in medical, is fused deposition modeling/FDM, because capable of producing its porosity high with a pattern laydown and the mechanical force good. However, FDM technology have some drawbacks i.e. the use of single type material, limited types of materials, and operation at high temperatures. This research was conducted to develop pre-surgery implants based on additive manufacturing technology to reconstruct and redesign cranial bone defects in Indonesia. This research produced 3D printer-based of injection moulding method by modifying tools, materials, steps, and pre-surgery implants production system based on the additive manufacturing for cranioplasty. Geomatrical accuracy of implant was measured in term of volume deviation, thickness deviation, linear length deviation and surface curve angle deviation of implants. The study comparing two different methods tested: cranial/intra-operative method and injection moulding method using PMMA material. The result showed that implant manufactured by 3D printer based mould have a higher geometrical accuracy as compared to cranial method. Volume deviation on the produced implants is 1.87 ± 1.27 % (injection moulding) compared to 11.39 ± 3.71 % (cranial method), thickness deviation of 2.54 ± 0.86 % (injection moulding) compared to 7.35 ± 1.43 % (cranial method), linear length deviation of 2.61 ± 0.47% (injection moulding) compared to 5.76 ± 0.79 % (cranial method), curve length deviation of 1.54 ± 0.77% (injection moulding) compared to 6.34 ± 0.99 % (cranial method) and surface curve angle deviation of 0.98 ± 0 % (injection moulding) compared to 15.45 ± 3.94 % (cranial method). From the data, it can be concluded that the injection moulding method is better suited than the cranial/intra-operative method.